Експериментальне дослідження працездатності колінчастих валів та циліндро-поршневих груп дизелів авіаційної наземної техніки - Приймаков, Олександр Григорович; Градиський, Юрій Олександрович (НТУ "ХПІ", 2006)
In this article there are results long-term tests of diesel engines of the aviation ground technique. It has the purpose of determination of supply of operating properties that provide efficiency and reliability of details and assembling units within the limits of guarantee work
Keywords: авіаційна наземна техніка; дизельни двигуні; апостеріорне прогнозування; в'язкість моторних мастил; витрата палива